A serial of novel four degrees of freedom parallel mechanisms with large rotational workspace. Issue 4 (9th July 2014) - Guo, Sheng; Ye, Wei; Qu, Haibo; Zhang, Dan; Fang, Yuefa
SUMMARY: In this paper, a class of novel four Degrees of Freedom (DOF) non-overconstrained parallel mechanisms with large rotational workspace is presented based on screw theory. First, the conflict between the number of independent constraints applied on the moving platform and the number of kinematic limbs for 4-DOF non-overconstrained parallel mechanism is identified. To solve this conflict, the platform partition method is introduced, and two secondary platforms are employed in each of the parallel mechanisms. Then, the motion requirements of the secondary platforms are analyzed and all the possible kinematic chains are enumerated. The geometrical assembly conditions of all possible secondary limbs are analyzed and some typical non-overconstrained parallel mechanisms are generated. In each of the parallel mechanisms, a planetary gear train is used to connect both of the secondary platforms. The large rotational workspace of the moving platform is obtained due to the relative motion of the two secondary platforms. Finally, the kinematics analysis of a typical parallel mechanism is conducted.